Acute effects of intravenous cocaine administration on serum concentrations of ghrelin, amylin, glucagon-like peptide-1, insulin, leptin and peptide YY and relationships with cardiorespiratory and subjective responses. (1st November 2017) - Bouhlal, Sofia; Ellefsen, Kayla N.; Sheskier, Mikela B.; Singley, Erick; Pirard, Sandrine; Gorelick, David A.; Huestis, Marilyn A.; Leggio, Lorenzo
Highlights: Appetitive hormones were examined in cocaine users after intravenous (IV) cocaine administration. Glucagon-like peptide-1 (GLP-1) and peptide YY (PYY) serum concentrations decreased 60 min after IV cocaine administration. Such changes were linked to cardiorespiratory and subjective responses to IV cocaine. Abstract: Background: Food intake and use of drugs of abuse like cocaine share common central and peripheral physiological pathways. Appetitive hormones play a major role in regulating food intake; however, little is known about the effects of acute cocaine administration on the blood concentrations of these hormones in cocaine users. Methods: We evaluated serum concentrations of six appetitive hormones: ghrelin (total and acyl-ghrelin), amylin, glucagon-like peptide-1 (GLP-1), insulin, leptin and peptide YY (PYY), as well as acute cardiorespiratory and subjective responses of 8 experienced cocaine users who received 25 mg intravenous (IV) cocaine. Results: Serum concentrations of GLP-1 ( p  = 0.014) and PYY ( p  = 0.036) were significantly decreased one hour following IV cocaine administration; there was a trend towards a decrease for insulin ( p  = 0.055) and amylin ( p  = 0.063) concentrations, while no significant IV cocaine effect was observed for ghrelin (total or acyl-ghrelin) or leptin concentrations ( p ' s ≫>  0.5). We also observed associations between hormone concentrations acutely affected by IV cocaine (GLP-1, PYY, insulin, amylin) and some cocaine-related cardiorespiratory and subjective responses ( e.g ., increased heart and respiratory rates; feeling high and anxious). Discussion: These findings show a significant effect of acute IV cocaine administration on some appetitive hormones and suggest potential associations between these hormones and cocaine-related cardiorespiratory and subjective responses. Additional research is needed to further investigate the potential mechanisms underlining these associations.